The Use of Plants, Nanotechnology and Surfactants in Lindane Remediation: A Mini Review (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Lindane is an organochlorine chemical and an isomer of hexachlorocyclohexane that has been used both as an agricultural insecticide and as a pharmaceutical treatment for lice and scabies. Lindane accumulates in the agricultural soil and plants thereby causing environmental and health deteriorative effects. A lot of soil remediation methods used are highly expensive and require a lot of expertise. Phytoremediation (rhizofiltration, phytostabilization), which involve the use of the plant to stabilize or remove environmental toxicants is presently much in use because of its cost-effectiveness and ecological friendliness. Adsorption has emerged as the most efficient, easy, and promising nanotechnology method of wastewater treatment out of the several approaches now employed. Recently, biosurfactants are used for the production of nanoparticles which will be further applied in the area of pesticide remediation. The use of phytoremediation is the most important fully green approach as no new chemicals are added to the polluted soil. Other emerging technologies where phytoremediation might not be applicable especially groundwater has begun to evaluate the use of green nanobiotechnology.
Keywords: Plants Phytoremediation Nanotechnology Surfactants Lindane Remediation